Linking Together Independent Sustainable Building Development Plans. (June 2019) - Sůra, M
Abstract: The contribution describes two basically independent projects, both claiming to be oriented on sustainable building paradigms. The two projects had investors of two different types – one using public money to the benefit of community, the other was purely private money of a private economic operator. Both investors examined the sustainability in relation to the surrounding conditions and processes, discovered the concurrent existence of the other's investment plans, and determined overlapping areas of interest. In the article we describe the overlapping areas, variant solutions intended to improve sustainability for lower costs, the pros and cons of the variants, and the harmonization of both investors' requirements. This was used to choose the variant best fitting both investors, and finally modify it slightly.